You're hired! : putting your sociology major to work - Joseph, Cheryl (Emerald Publishing Limited, 2017)
Featuring conversations with more than thirty sociology majors on their career trajectories, responses from employers on why they hire sociology majors, and practical career advice, You're Hired! Putting Your Sociology Major to Work offers readers a comprehensive account of the opportunities a sociology major provides. The book begins with the conversations, which convey real world examples of sociologists' motivations for pursuing the discipline, their career paths, the joys and challenges of their choices, and their advice to current and future students of sociology. Their careers range from politics and technology to medical research and community activism; business and the arts to sports and the environment, all which demonstrate the breadth of career options available to sociology majors. Later chapters present feedback from employers on the skills sociologists to the workplace along with guidance on career entry and professional development. Those interviewed cover a broad spectrum of society and career progression; some are on the starting block of their careers while others look back from retirement on fulfilling and meaningful professional lives. They represent regional, gender, racial, and the social class reality of today's world. Written in an accessible and upbeat style, You're Hired! is an informative and inspiring read for current undergraduates, aspiring students, and parents alike.